If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 6 + 4(3m + -5) + -5(m + 5) = 0 Reorder the terms: 5m + 6 + 4(-5 + 3m) + -5(m + 5) = 0 5m + 6 + (-5 * 4 + 3m * 4) + -5(m + 5) = 0 5m + 6 + (-20 + 12m) + -5(m + 5) = 0 Reorder the terms: 5m + 6 + -20 + 12m + -5(5 + m) = 0 5m + 6 + -20 + 12m + (5 * -5 + m * -5) = 0 5m + 6 + -20 + 12m + (-25 + -5m) = 0 Reorder the terms: 6 + -20 + -25 + 5m + 12m + -5m = 0 Combine like terms: 6 + -20 = -14 -14 + -25 + 5m + 12m + -5m = 0 Combine like terms: -14 + -25 = -39 -39 + 5m + 12m + -5m = 0 Combine like terms: 5m + 12m = 17m -39 + 17m + -5m = 0 Combine like terms: 17m + -5m = 12m -39 + 12m = 0 Solving -39 + 12m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + 12m = 0 + 39 Combine like terms: -39 + 39 = 0 0 + 12m = 0 + 39 12m = 0 + 39 Combine like terms: 0 + 39 = 39 12m = 39 Divide each side by '12'. m = 3.25 Simplifying m = 3.25
| 7x+-4=1x+32 | | 12n+2(n-3)=1+5(2n-1) | | 12x+11y=18 | | 4b+3-b=4(b-5)+2 | | 0.4(p+1)-0.9(p+5)=-2 | | (2x^2+3x-6)-(x^2-18x+6)= | | -250+5(5)= | | 6(7x+9)=264 | | 6(3+k)=48 | | c-(-75)=25 | | -250+5(3)= | | 4(h+8)=16 | | 6-4u=2 | | a(6a^2+2a+9)= | | 6(2-x)=20 | | 21-11y=7 | | 2x-10(2x-1)=5 | | 0.5x+58=-23 | | 7y=210 | | -6x-7=29 | | 250=x*1000 | | 6x+2x-5=43 | | (X-3)(X+3)=6x^2-14 | | 5+3(4x-2)=-18 | | a+7=11 | | 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= |